Toolbuddy digital platform – A conceptual solution in peer-to-peer rental marketplace for tools and equipment in Malaysia - Ahmad Faris, Muaz; Azmir, Mohammad Hafzan; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2017)
This paper proposes a conceptual solution to encourage sharing economy as a new disruptive economic force nowadays by providing an online digital tool-sharing platform, named ToolBuddy. ToolBuddy is a Consumer-to-Consumer (C2C) business model which aims to provide an online platform for tool-owners and renters for peer-to-peer sharing of their tools and equipment in short term from a nearby location. This platform provides opportunities to rental provider company to feature their tools and equipment. Conducting Literature Review and benchmarking against current world leading companies that provide tool-sharing solutions by utilizing the nine blocks of Business Model Canvas (BMC) and Value Proposition Design Canvas (VPCs) framework, establishing Strategy Canvas of key competitors, identify solution gaps, and establishing the Environmental Map that incorporates megatrends, and Industry 4.0 have been used as the methodology for this paper.